Comparison of brain gray and white matter macromolecule resonances at 3 and 7 Tesla. Issue 3 (22nd September 2014) - Snoussi, Karim; Gillen, Joseph S.; Horska, Alena; Puts, Nicolaas A. J.; Pradhan, Subechhya; Edden, Richard A. E.; Barker, Peter B.
<x xml:space="preserve">Abstract</x> Purpose In proton MR spectra of the human brain, relatively broad macromolecule (MM) resonances underlie the narrower signals from metabolites. The purpose of this study was to quantify the MM profile in healthy human brain at 3T and 7T, both in gray matter (anterior cingulate cortex [ACC]) and white matter (centrum semiovale [CSO]). Methods A water‐suppressed, inversion‐recovery pulse sequence was used to null metabolite signals and acquire MM spectra in 20 healthy volunteers using very similar methodology at both field strengths (n = 5 per region and field). The MM spectra were fitted with multiple Gaussian functions and quantified relative to the unsuppressed water signal from the same volume. Results MM proton concentration values were in the range of 5–20 mmol/kg. No significant differences were found between the MM proton concentration measurements by region (P ≈ 0.8) nor by field strength (P ≈ 0.5). Linewidths of the well‐resolved M1 peak were slightly more than double at 7T (43.0 ± 4.7 Hz in ACC, 45.6 ± 4.1 Hz in CSO) compared with 3T (19.8 ± 3.5 Hz in ACC, 20.0 ± 4.3 Hz in CSO). Conclusion The absence of differences in MM concentrations between white and gray matter implies that a single MM "baseline" may be adequate for spectral fitting of multiple brain regions when determining metabolite concentrations. Visibility of MM signals is similar at 3T and 7T. Magn Reson Med 74:607–613, 2015. © 2014 Wiley Periodicals, Inc.